The role of Jatmika Reading House volunteers in instilling children’s environmental literacy - Srikandina, Dita; Anwar, Rully Khairul; Rohman, Asep Saeful (Jurnal Kajian Informasi dan Perpustakaan, 2024)
Jatmika Reading House is a community library that actively teaches environmental literacy through various activities, one of which is eco-enzyme making. This study aims to explore the role of volunteers in eco-enzyme making, identify the challenges faced during the activity, and understand the motivation of volunteers in contributing to Jatmika Reading House's activities. This research used a qualitative method with a case study approach. The informants in this study were two volunteers who were selected through a purposive sampling technique due to their direct involvement in eco-enzyme-making activity. Data collection techniques included interviews, indirect observation, documentation, and literature review. This research is important because although environmental education has developed, there are still few studies that specifically discuss the role of volunteers in teaching environmental literacy to children. In fact, volunteers have a strategic role in introducing the concept of sustainability and building environmental awareness through community activities. The results showed that volunteers acted as facilitators, mentors, instructors, encouragers, and organizers of children's participation. They faced various challenges, such as unconducive conditions due to limited tools and materials and an inadequate number of volunteers, resulting in less optimal activity management. Volunteers' motivations varied, ranging from the satisfaction of sharing knowledge and commitment to improving community literacy to personal happiness in social interaction. The findings from this study are expected to provide new insights to strengthen environmental literacy programs involving volunteers.